Pagod na ako, Irog [videorecording] - Jacob, Marilou; Communication Foundation for Asia. ([Manila] Communication Foundation for Asia, 1997)
A docu-drama on the life and works of the controversial national artist, and labor leader, Amado V. Hernandez, with narratives by the people who knew him best - Atang dela Rama, Carlos P. Romulo and Salvador Lopez.
Johnny Delgado, Lirio Vital.
Keywords: Hernandez, Amado V; Labor relations; Biography